Identities as protective processes: Socio-ecological perspectives on youth resilience - Chen J. (2017)
Identity formations are critical developmental accomplishments in negotiating resilience. They involve establishing cohesive senses of self and appraisals of inherent personal strengths and weaknesses in contexts of environmental offerings. Further, identity processes call upon understanding the collective beliefs and values of one's community. Using Day in the Life semi-naturalistic videos, photo elicitation and interview data, we observed four at risk but resilient migrant adolescents in two different cultural contexts (Vancouver, Canada, and Chiang Mai, Thailand) and inspected relationships between their identity formations (personal, social, cultural, and religious) and their positive participation in, and personal interpretations of, their social relationships and cultural engagements. We ask how and in what fashion the youths' identities, practices, and perspectives might serve protective functions, especially in the face of significant geographic dislocation. © 2012 Taylor & Francis.